2016
DOI: 10.1111/sji.12476
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Levels After Consumption of a Medicinal Agaricus blazei Murill‐Based Mushroom Extract, AndoSan, in Patients with Crohn's Disease and Ulcerative Colitis in a Randomized Single‐Blinded Placebo‐Controlled Study

Abstract: Ingestion of the Agaricus blazei Murill-based mushroom extract AndoSan has been shown in randomized placebo-controlled studies to improve symptoms in Crohn's disease (CD) and ulcerative colitis (UC) and also fatigue and quality of life in the latter patients. The aim was to examine whether this clinical impact of AndoSan intake could be explained by influence on foremost pro-inflammatory cytokines in the patients. Fifty patients with symptomatic UC and CD were randomized and blinded for oral daily intake of An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…A decrease in plasma levels of pro-inflammatory cytokines has been observed in IBD patients after oral intake of a mushroom extract isolated from a mixture of basidiomycetes mushrooms Agaricus blazei Murill, Hericium erinaceum , and Grifola frondosa. However, these anti-inflammatory effects have been marginal and not reproducible for all patients [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decrease in plasma levels of pro-inflammatory cytokines has been observed in IBD patients after oral intake of a mushroom extract isolated from a mixture of basidiomycetes mushrooms Agaricus blazei Murill, Hericium erinaceum , and Grifola frondosa. However, these anti-inflammatory effects have been marginal and not reproducible for all patients [ 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, processing of the mushroom may determine the effect produced on immune cells, possibly due to different solubility and potency of specific compounds [ 10 , 11 ]. Edible mushrooms have been studied extensively for their immune modulating properties in animal models including β-glucan-induced anti-inflammatory effects [ 3 , 12 ], enhanced NK cell activity [ 11 , 13 ], improved dendritic cell (DC) maturation and function [ 14 ], increased cytokine production [ 15 ], increased protective immunity from Salmonella vaccination [ 16 ], and anti-inflammatory effects in patients with ulcerative colitis and Crohn’s disease [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Treatments include the use of immunomodulators. Norwegian scientists reported that ingestion of an Agaricus blazei mushroom extract AndoSan™ improved symptoms in patients suffering from Crohn’s disease and the related malady ulcerative colitis [ 217 , 218 ]. The authors suggest that because the treatment did not seem to cause any adverse effects, the mushroom preparation has the potential to be used as a safe supplement to conventional medication.…”
Section: Anticancer Effectsmentioning
confidence: 99%
“…Another study suggested that Chaga mushroom extract can protect DNA against the oxidative damage in the lymphocytes of IBD patients [ 27 ]. AndoSan™ has also been applied in another randomized placebo-controlled study; however, these 50 patients exhibited active UC and CD, and only limited anti-inflammatory effects were observed in these patients [ 28 ].…”
Section: Effects Of Nsps On Ibdmentioning
confidence: 99%